P5-S5.02 Outcomes following the introduction of HIV partner notification guidelines in Edmonton, Canada. (10th July 2011) - Bergman, J; Brandley, J; Gratrix, J; Ross, K; Paradis, K; Parker, P; Anderson, B; Houston, S; Singh, A
Abstract : Background: In April 2010, the HIV Partner Notification Guidelines were implemented in Edmonton, Alberta, Canada. Prior to this, partner notification of newly diagnosed HIV cases was conducted inconsistently. Methods: All individuals newly diagnosed with HIV in the Alberta Health Services- Edmonton zone were interviewed by a partner notification nurse (PNN) for sexual and needle sharing partners, and perinatal contacts under Alberta's Public Health Act. PNNs attempted to locate named contacts to ensure timely counselling, testing, and follow-up care. The number of contacts in the year preceding the diagnosis and information required to locate each contact was recorded for each case. Additional information included whether they were located, tested, and their test results; all information was entered into a Notifiable Disease Reporting database. A descriptive analysis was performed on the characteristics and outcomes of data collected between 5 April and 31 December 2010. Results: There were 50 newly diagnosed HIV cases during this time period. The majority (n=33; 66%) of the cases were male and the overall median age was 39 years (IQR 32–48). Male cases were more likely to be Caucasian (n=21; 63.6%) while female cases were more likely to be Aboriginal (n=8; 47.1%, p=0.001). The primary mode of transmission among male cases was MSM (n=18; 54.5%) and among female cases was heterosexual transmission (n=10; 58.8%). A total of 92 contacts were provided by 36 (72%) of the HIV cases, with an average of 2.6 (range 1–14) contacts per case. The majority (97.8%; n=90) of contacts were exposed through sex with an additional 5 (5.4%) contacts being exposed through needle sharing during drug use. Of the 92 named contacts, 17.4% (n=16) were found to be previously positive for HIV, 16.3% (n=15) resided outside of Edmonton, and the remaining 66.3% (n=61) were followed up by local PNNs. At the time of analysis, 75.4% (n=45) of the contacts were located and of those located, 82.6% (n=38) were tested resulting in four new cases of HIV. Conclusions: HIV partner notification efforts resulted in the majority of contacts being located and tested for HIV, with four new cases of HIV identified. Nearly one-quarter (n=20; 21.7%) of the total contacts were HIV positive, suggesting a need for ongoing prevention and risk reduction strategies for individuals living with HIV and their partners.